Multiple obesity indices suggest a close relationship between obesity and constipation: evidence from NHANES - Nengjun Xiang; Lulu Xu; Haihua Qian; Dan Zhang (BMC, 2024)
Abstract Objective This study aims to investigate the relationship between obesity and constipation among American adults. Methods Our study leveraged data from the National Health and Nutrition Examination Survey (NHANES). This comprehensive approach enabled us to summarize the weighted prevalence rates of obesity in adults. To further deepen our understanding, we employed a variety of analytical methods. These included multivariable logistic regression, subgroup analysis and restricted cubic splines. Through these methodologies, we were able to effectively evaluate the correlation between various obesity indicators and constipation, offering new insights into this complex relationship. Results The weighted prevalence of constipation stands at 9.42%. Notably, an increased risk of constipation is linked with a BMI (body mass index) exceeding 28 kg/m2, WSR (waist-stature ratio) that is either between 58.3 and 64.8 or above 64.8, as well as a LAP (lipid accumulation products) ranging from 50.8 to 90.1. In contrast, a reduced risk of constipation is associated with WWI (weight-adjusted-waist index) that falls between 0.015 and 0.020, exceeds 0.020, and without the presence of central obesity (P < 0.05). Restricted cubic spline analysis, a significant non-linear relationship was discerned between BMI, WSR, and LAP in relation to constipation. Conclusions This pioneering large-scale study explores the relationship between various obesity indices and constipation. It reveals that reducing the BMI, WSR, LAP and waist circumference can decrease the risk of constipation. Conversely, a higher value of WWI correlates with a lower constipation risk, and this remains true even after adjusting for a wide range of variables.